Experiential learning in community pharmacy: online and remote teaching experience in Malaysian higher education - Ab Rahman, Norny Syafinaz; Nazar, Nor Ilyani; Elnaem, Mohamed Hassan Abdelaziz (International Pharmaceutical Federation (FIP), 2020)
Experiential learning provides opportunities for students to learn beyond the classroom setting. Due to the COVID-19 pandemic, students were unable to complete their attachment modules in community pharmacy settings, thus a four week community pharmacy course was conducted via remote learning. Students were required to have a maximum of two hours of virtual discussion and consultation sessions with a faculty member (with community pharmacy background/experience) twice a week. In each week, students were required to complete all tasks given based on the activities proposed in the community pharmacy logbook. MyDispense (an online pharmacy simulation) and Access Pharmacy (McGraw-Hill) were utilised by students to practice their dispensing skills and familiarisation with non-prescription medications, respectively. Case discussions on responding to minor ailments were also touched on during the online sessions. Students were assessed via logbook, preceptor assessment and an online objective structured clinical examination (OSCE).